Textbook of Cardiovascular Intervention - Thompson, Craig A. (Springer London : Imprint: Springer, 2014)
Catheter-based interventions have evolved to address a variety of needs through innovation and clinical evidence. The field of interventional cardiology and interventional vascular medicine now comprises the dominant diagnostic and therapeutic field within cardiovascular medicine, and continues to grow in terms of patients managed and physicians trained. Given the vast expansion of technologies, techniques, and the clinical evidence base, it can be challenging for the practicing clinician, fellow-in-training, or technology developer to maintain general knowledge of the interventional cardiovascular field. The Textbook of Cardiovascular Intervention is intended to provide a practical, comprehensive and compact text on interventional cardiology for the current, rapidly evolving practice environment. It will appeal to fellows, residents and physicians in cardiology, interventional cardiology, cardiothoracic and vascular surgery, vascular and endovascular medicine, neurointerventional radiology and surgery, emergency medicine and intensive care.